THE INFLUENCE OF SERVICE QUALITY ON PATIENT SATISFACTION AND IMPLICATIONS FOR PATIENT CONFIDENCE IN IMMANUEL HOSPITAL OUTPATIENT CENTER - Yofy Syarkani; Noveline Sagita; Tamy Ali Januarty (Jurnal Scientia, 2023)
The quality of service in hospitals consists of five dimensions such as tangible, reliability, responsiveness, assurance, and empathy. With improvement in service quality, customer satisfaction is expected to increase, and hospitals can successfully gain patients' trust. This study aims to determine the effect of service quality on satisfaction and its implications for patient trust. This cross-sectional study is conducted in the outpatient center in Immanuel Hospital, Bandung, on August 2022. A five-point Likert scale questionnaire was distributed to 100 respondents who met the inclusion and exclusion criteria. The data obtained were then analyzed descriptively (respondent demographic data, patient perceptions of service quality, patient satisfaction, and trust) and an analytical study was done using Structural Equation Modeling (SEM) analysis with Lisrel 8.8. The majority of respondents are women, housewives, aged 41-60 years, with 9 years of educational background. The data obtained show that the patient’s perception of service quality is good, patient satisfaction is fairly satisfied and patient trust in the hospital is quite trusting. Of the five dimensions that make up service quality, empathy has the highest percentage (73,67%). All dimensions of service quality simultaneously affect patient satisfaction directly by 72,4%. Patient satisfaction directly affects patient trust by 75,20%. The degree of service quality contribution to the patient trust, through patient satisfaction, is 0,851. There is a positive influence between service quality and patient satisfaction, between patient satisfaction and patient trust. Improving service quality will increase patient trust in the hospital, through patient satisfaction.